STRATEGI PENGUATAN KARAKTER RELIGIUS SISWA DI ERA DIGITAL - Achmad Iqfani; A. Faizul Mubarak (LPPM STAI Muhammadiyah Probolinggo, 2026)
The rapid development of digital technology has transformed students’ religious life by providing broader access to religious information while simultaneously increasing the risk of moral degradation, exposure to non‑credible religious content, hoaxes, and hate speech. These conditions require educational strategies that go beyond cognitive religious instruction to foster a strong, critical, and digitally adaptive religious character. This study aims to conceptually formulate a comprehensive strategy for strengthening students’ religious character in the digital era by examining the nature of students’ religious character, the supporting and inhibiting factors, and the most relevant strengthening strategies. This research employs a qualitative descriptive approach through library research, analyzing 30 scientific articles, academic books, and policy documents published between 2021 and 2025 related to religious character, character education, and educational digitalization. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing, supported by source triangulation and peer review to ensure validity. The findings indicate that effective strengthening of religious character requires the integration of several key pillars: digital religious literacy, religious habituation, teacher role‑modeling, collaboration among schools, families, and communities, and the purposeful use of digital technology within the curriculum and school culture. Theoretically, this study proposes an integrative and context‑sensitive model of religious character strengthening aligned with the digital ecosystem, which extends the application of social learning theory into digital environments. Practically, the model can serve as a theoretical and strategic reference for schools, teachers, and policymakers in designing more systematic, collaborative, and digitally relevant religious character education programs for students.